(untitled) (Research, Society and Development, 2024)
This article investigates the intersection between the COVID-19 pandemic and arboviruses like dengue and Chikungunya, exploring the combined impacts and public health responses. The central objective is to analyze how the pandemic influenced the epidemiology of arboviruses, highlighting the diagnostic difficulties in coinfections and the effectiveness of public health measures. We employed an integrative review methodology, examining studies published between 2019 and 2024 that discussed the interaction between COVID-19 and arboviruses, changes in health systems, and the impact of non-pharmaceutical interventions during the pandemic period. The results indicate that social isolation measures to control COVID-19 had unintended effects in reducing the transmission of arboviruses. Additionally, the pandemic challenged health systems by redirecting resources that worsened arbovirus management but also offered an opportunity for reforms that could strengthen responses to multiple epidemics. The discussion emphasizes the need for accurate diagnoses to avoid errors in treating coinfections and suggests that the pandemic experience can be a catalyst for integrating more robust health strategies. We conclude that an integrated and adaptable public health approach is essential for managing the coexistence of multiple health threats, ensuring proper preparedness for future epidemiological crises.